The roles of university libraries in supporting the integration of information literacy in the course instruction - Maitaouthong, Therdsak; Tuamsuk, Kulthida; Tachamanee, Yupin (Malaysian Journal of Library and Information Science, 2017)
Maitaouthong, T., Tuamsuk, K., & Tachamanee, Y. (2012). The roles of university libraries in supporting the integration of information literacy in the course instruction. Malaysian Journal of Library & Information Science, Vol.17, no. 1: 51-64. A number of research studies have been conducted related to information literacy in universities. The findings indicated the roles of libraries in information literacy education by means of the arrangement of information literacy activities for students, such as orientation, short training programme, teaching at the reference desk, online self learning programme and co-teaching in class. This research was aimed at studying the roles of university libraries in the support of information literacy integration in the course instruction. Two research approaches, a survey and a focus group were used. Data were collected from 42 academic librarians by using the questionnaires and then confirming the data by conducting a focus group interview with 15 experts in the field of library and information science, curriculum and instruction, and general education. The findings indicate that university libraries are the important organisation with the roles to teach and support the integration of information literacy in the instruction of various undergraduate courses. Libraries have 4 major roles, namely, (a) preparation of resources and learning sources, (b) supporting the teaching of information literacy of educators and librarians, (c) organising learning and teaching activities that develop students’ information literacy, and (d) organising activities to develop educators’ information literacy. It is suggested that library administrators take the roles to prepare library infrastructures and resources necessary for the integration of information literacy. Librarians should be trained to be able to effectively teach in courses and organise the activities to promote knowledge and understanding of information literacy among educators and students.